EAHP Survey 2010 on hospital pharmacy in Europe: Part 1. General frame and staffing. Issue 4 (30th August 2012) - Frontini, Roberto; Miharija-Gala, Tajda; Sykora, Juraj
Abstract : In 2010, the European Association of Hospital Pharmacists (EAHP) conducted its fourth survey on hospital pharmacy practice in Europe. 4748 heads of pharmacy were contacted in all member states through a network of national coordinators. 1283 hospital pharmacies from 30 countries answered the questionnaire with an overall response rate of 27.0%. The average number of beds served by one pharmacy had not changed since 2005 but there was a decrease in complete and an increase in partial hospitalisation. Pharmacists (27%) and qualified technicians (32%) make up 60% of the total staff. The number of pharmacists/100 beds varies from 0.24 (Bosnia and Herzegovina) to 4.35 (UK). Only a few countries did not experience shortages of pharmacists and technicians. European hospital pharmacy staffing (pharmacists and pharmacy technicians) remains, on average, low compared with the USA and has not grown significantly since 1995. Therefore, it can be problematic to make direct comparisons between hospital pharmacy services in the USA and Europe.